Implementation of Learning Models Picture and Picture in Improving Indonesia Language Learning Outcomes "My Environtment" Material for School UPT 060822 Medan - Hasnah Harahap, Poppy; Sutikno; Rahmat Kartolo; Irma Masithah; Heny Triana (International Journal of Educational Research Excellence (IJERE), 2026)
This research is motivated by the low learning outcomes of Indonesian language of grade IV students of UPT SD Negeri 060822 Medan City on the material "My Surrounding Environment". The learning method that is still dominated by lectures causes students to be less active and unmotivated in the learning process. Therefore, this study aims to implement the Picture and Picture learning model to improve student learning outcomes. This study uses the Classroom Action Research (CAR) method with a repeated cycle design, consisting of planning, action, observation, and reflection stages. The subjects of the study were 20 fourth-grade students of UPT SD Negeri 060822 Medan City in the 2025-2026 academic year. Data collection techniques were carried out through observation, tests, and interviews, while data analysis used quantitative and qualitative approaches. The results of the study showed an increase in student learning outcomes. At the pretest stage (initial conditions), the average student score was 66.5 with a completion rate of 20%. After the application of the Picture and Picture model in cycle I, the average score increased to 74.5 with a completion percentage of 60%. In cycle II, the average score increased again to 87 with a completion percentage reaching 95%. Based on the results of the study, it can be concluded that the application of the Picture and Picture model is effective in improving the Indonesian language learning outcomes of fourth-grade students. This model not only helps students' understanding through image media, but also encourages them to be more active in the learning process. Therefore, the Picture and Picture model is recommended to be applied in Indonesian language learning to improve student learning outcomes